2017
DOI: 10.1007/s10620-017-4605-z
|View full text |Cite
|
Sign up to set email alerts
|

Medical Management of Pain in Chronic Pancreatitis

Abstract: The medical management of pain in chronic pancreatitis continues to pose significant challenges for clinicians caring for these patients. There are increasing data, suggesting that pain in chronic pancreatitis is largely due to peripheral and central sensitization that evolves, over time, as a result of nociceptive afferent associated with chronic inflammation and fibrosis of the pancreas. In many instances, patients rapidly progress to requiring opioid analgesics for the adequate treatment of pain despite the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…37,39,40 In many cases, patients rapidly progress to requiring opioid analgesia, despite the risks associated with its long-term use. 40 This may be one of the causes of correlations between the intensity of pain and its impact on QoL, which has been confirmed by the results of studies by Fitzsimmons et al 5 and Solomina et al, 41 which showed that patients who take opioids have a poorer QoL. 5,41 Pain management is the main and predominant therapeutic challenge in CP, requiring a biopsychosocial approach focusing on interventions tailored to the needs of the individual patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…37,39,40 In many cases, patients rapidly progress to requiring opioid analgesia, despite the risks associated with its long-term use. 40 This may be one of the causes of correlations between the intensity of pain and its impact on QoL, which has been confirmed by the results of studies by Fitzsimmons et al 5 and Solomina et al, 41 which showed that patients who take opioids have a poorer QoL. 5,41 Pain management is the main and predominant therapeutic challenge in CP, requiring a biopsychosocial approach focusing on interventions tailored to the needs of the individual patient.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic pancreatitis pain has both peripheral and central elements and is often due to nociceptive stimulation caused by chronic inflammation and fibrosis of the pancreas 37,39,40 . In many cases, patients rapidly progress to requiring opioid analgesia, despite the risks associated with its long-term use 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdominal pain is the hallmark symptom of chronic pancreatitis (CP), affecting more than 80% of patients, is associated with lower quality of life and is difficult to treat for several reasons (1). First, there are no accurate diagnostic tests that enable clinicians to differentiate between highly prevalent functional gastrointestinal disorders (2) and early CP (3,4).…”
mentioning
confidence: 99%